Neurotoxicity and acute oxalate nephropathy in a Chronic kidney disease patient due to plant toxin (Bilimbi fruit -Averrhoabilimbi) : case report from a primary care center of Bangladesh (Bangladesh Journal of Medicine, 2024)
Averrhoabilimbi, commonly known as bilimbi fruit, belongs to the family of Oxalidaceae and share similar physical and biochemical characteristics to star fruit, which is a well recognized cause of acute oxalate nephropathy and neurotoxicity. There are few reported individual cases regarding neurotoxicity and oxalate nephropathy, due to ingestion of bilimbi fruit, attributed to its high oxalate content and caramboxin like neurotoxin. But, till now there is no such reported case from a primary care center, to have both of these rare complications due to bilimbi fruit ingestion in a single patient. Here we report a case of a 62 years old lady, who presented with sudden onset behavioral changes, agitation, confusion, followed by acute symptomatic seizure and subsequently acute kidney injury and its complications following ingestion of bilimbi fruit. After meticulous history taking and thorough evaluation, she was diagnosed with aforementioned diagnosis and later on successfully managed in the limited resource facility.Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 174-175